An energy efficient mobile device for assisted living applications - Fudickar, Sebastian; Frohberg, M; Taube, S; Mahr, P; Schnor, B (2012 IEEE Online Conference on Green Communications, GreenCom 2012, 2012)
Common problems of many elderly include falling accidents and getting lost while leaving their common surroundings unattended. We developed a mobile device that includes indoor localization based on the energy-efficiency Sub 1GHz wireless communication via radio signal strength (RSS) measurements and fall detection functionality. Power management is a critical part for the success of such a device. The authors suggest the use of Sub 1GHz transceivers (using the 433, 868 or 915 MHz frequency bands) with their optimized energy characteristics and increased transmission ranges for localization and emergency calls in case of a fall. Therefore, we present a hardware design of an energy efficient mobile device, the so-called EMU, that includes Sub 1GHz and Wi-Fi transceivers. An optimization of the Wi-Fi localization increased the uptime from 7 h to 9:25 hours. Further, the utilization of Sub 1GHz for localization has more than doubled the uptime to 21 hours, as shown in two benchmarks (measuring perchip power-consumption and system uptime while performing network communication), while achieving a comparable location accuracy.